Contrast Tempo of Movement and Its Effect on Power Output and Bar Velocity During Resistance Exercise - Wilk, Michal; Jarosz, Jakub; Krzysztofik, Michal; Filip-Stachnik, Aleksandra; Bialas, Marcin; Rzeszutko-Belzowska, Agata; Zajac, Adam; Stastny, Petr (Frontiers in physiology, 2020)
In this study, we examined the impact of contrast movement tempo (fast vs. slow) on power output and bar velocity during the bench press exercise. Ten healthy men (age = 26.9 ± 4.1 years; body mass = 90.5 ± 10.3 kg; bench press 1RM = 136.8 ± 27.7 kg) with significant experience in resistance training (9.4 ± 5.6 years) performed the bench press exercise under three conditions: with an explosive tempo of movement in each of three repetitions (E/E/E = explosive, explosive, explosive); with a slow tempo of movement in the first repetition and an explosive tempo in the next two repetitions (S/E/E = slow, explosive, explosive); and with a slow tempo of movement in the first two repetitions and an explosive tempo in the last repetition (S/S/E = slow, slow, explosive). The slow repetitions were performed with a 5/0/5/0 (eccentric/isometric/concentric/isometric) movement tempo, while the explosive repetitions were performed with an X/0/X/0 (X- maximal speed of movement) movement tempo. During each experimental session, the participants performed one set of three repetitions at 60%1RM. The two-way repeated measures ANOVA showed a statistically significant interaction effect for peak power output (PP; p = 0.03; η2 = 0.26) and for peak bar velocity (PV; p = 0.04; η2 = 0.24). Futhermore there was a statistically significant main effect of condition for PP (p = 0.04; η2 = 0.30) and PV (p = 0.02; η2 = 0.35). The post hoc analysis for interaction revealed that PP was significantly higher in the 2nd and 3rd repetition for E/E/E compared with the S/S/E (p < 0.01 for both) and significantly higher in the 2nd repetition for the S/E/E compared with S/S/E (p < 0.01). The post hoc analysis for interaction revealed that PV was significantly higher in the 2nd and 3rd repetition for E/E/E compared with the S/S/E (p < 0.01 for both), and significantly higher in the 2nd repetition for the S/E/E compared with the S/S/E (p < 0.01). The post hoc analysis for main effect of condition revealed that PP and PV was significantly higher for the E/E/E compared to the S/S/E (p = 0.04; p = 0.02; respectively). The main finding of this study was that different distribution of movement tempo during a set has a significant impact on power output and bar velocity in the bench press exercise at 60%1RM. However, the use of one slow repetition at the beginning of a set does not decrease the level of power output in the third repetition of that set.